Titanium copper foil, titanium copper strip and electronic component

By ensuring a uniform thickness in titanium copper foils with 1.5% to 5.0% Ti and a controlled standard deviation, the issues of unstable contact resistance and reduced fatigue resistance in electronic components are addressed, enhancing the performance and reliability of these components.

JP2025047759AActive Publication Date: 2025-04-03JX NIPPON MINING & METALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023156448
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

The uneven thickness of titanium copper foils leads to unstable contact resistance and reduced fatigue resistance in electronic components, particularly in connectors and spring materials.

Method used

The titanium copper foil is formulated with 1.5% to 5.0% by mass of Ti, with a standard deviation of foil thickness at nine points in a direction parallel to the rolling direction being 0.0100 or less, ensuring uniformity and reducing thickness variations.

Benefits of technology

The solution achieves significantly reduced variations in foil thickness, stabilizing contact resistance and enhancing fatigue resistance in electronic components, thereby improving the performance and reliability of connectors and other components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047759000001
    Figure 2025047759000001
  • Figure 2025047759000002
    Figure 2025047759000002
  • Figure 2025047759000003
    Figure 2025047759000003
Patent Text Reader

Abstract

To provide a titanium copper foil, a titanium copper strip and an electronic component having reduced foil thickness variation.SOLUTION: There is provided a titanium copper foil comprising 1.5 mass% to 5.0 mass% of Ti and the balance copper with inevitable impurities, wherein the ratio of the standard deviation (μm) of the foil thickness to the average value (μm) of the foil thickness at nine points located in a straight line at intervals of 10 mm in a direction parallel to the rolling direction is 0.0100 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This specification describes titanium copper foil, as well as titanium copper strips and electronic components containing the same. [Background technology]

[0002] Titanium copper foil has excellent stress relaxation properties and relatively high strength among copper alloy foils, and is therefore used in electronic device switches, connectors, jacks, terminals, relays, and other parts. In recent years, as electronic devices have become smaller, titanium copper foils with a thin foil thickness are required for use in electronic device parts. The foil thickness is, for example, 0.1 mm or less. Such a thin titanium copper foil is required to exhibit the required properties.

[0003] Patent Document 1 proposes "a titanium copper foil that contains 1.5 to 5.0 mass% Ti, with the remainder being copper and unavoidable impurities, has a foil thickness of 0.1 mm or less, and has a foil thickness variation of 0.0 μm to 1.0 μm at five measurement points spaced 60 mm apart in a direction parallel to the rolling direction" for the purpose of "providing a titanium copper foil and a manufacturing method thereof that exhibits little sagging when used as a spring even when the foil thickness is as thin as 0.1 mm or less and can be suitably used as a conductive spring material for use in electronic components such as autofocus camera modules." [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-179570 A Summary of the Invention [Problem to be solved by the invention]

[0005] If the thickness of the titanium copper foil is not uniform, when it is used in a connector, the contact pressure of the connector varies, and the contact resistance is not stable. As a result, poor contact may occur. Alternatively, if the thickness of the titanium copper foil is not uniform, when it is used as a spring material, the stress applied to the titanium copper foil is not uniformly distributed. As a result, the fatigue resistance of the electronic component may be reduced. From these viewpoints, it is necessary to further uniformize the thickness of the titanium copper foil.

[0006] This specification provides a titanium copper foil, a titanium copper strip, and an electronic component with reduced foil thickness variation. [Means for solving the problem]

[0007] The titanium copper foil of the present disclosure contains 1.5% by mass to 5.0% by mass of Ti, with the remainder being copper and unavoidable impurities, and has a ratio of the standard deviation (μm) of the foil thickness to the average foil thickness (μm) at nine points located on a line at intervals of 10 mm in a direction parallel to the rolling direction of the foil foil of 0.0100 or less.

[0008] The titanium copper foil of the present disclosure also contains 1.5% by mass to 5.0% by mass of Ti, with the remainder being copper and unavoidable impurities, and the standard deviation of the foil thickness at nine points located on a line at intervals of 10 mm in a direction parallel to the rolling direction is 0.500 μm or less.

[0009] The titanium copper strip of the present disclosure includes the titanium copper foil described above.

[0010] The electronic component of the present disclosure includes the titanium copper foil described above. Effect of the Invention

[0011] The titanium copper foil of the present disclosure has reduced variation in foil thickness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the above-mentioned titanium copper foil and the embodiment of the manufacturing method of the titanium copper foil will be described in detail.

[0013] In the present disclosure, "A to B" refers to "greater than or equal to A and less than or equal to B." A and B both represent numerical values.

[0014] In one embodiment, the titanium copper foil contains 1.5% to 5.0% by mass of Ti, with the remainder being copper and unavoidable impurities, and has a ratio of the standard deviation (μm) of the foil thickness to the average foil thickness (μm) at nine points located on a line at intervals of 10 mm in a direction parallel to the rolling direction of 0.0100 or less. With the above configuration, the influence of the foil thickness variation on the foil thickness is 1.00% or less, so it can be said that the variation is sufficiently reduced.

[0015] When a connector is manufactured using the titanium copper foil of the present disclosure, the thickness of the titanium copper foil is uniform, so that the variation in the contact pressure of the connector is suppressed and the contact resistance is stabilized, thereby effectively suppressing poor contact of the connector.

[0016] In order to manufacture a titanium copper foil with a uniform foil thickness as described above, it is essential to improve one or more cold rolling processes. Specifically, when performing a cold rolling process on a strip material obtained through melting, casting, and other processes, the feed speed of the strip material is measured by a laser speedometer when the strip material passes between the rolling rolls. Then, based on the measured value of the feed speed of the strip material measured by the laser speedometer, the roll gap between the rolling rolls is adjusted. This makes it possible to control the thickness of the strip material with high accuracy in the cold rolling process. As a result, the variation in foil thickness in the direction parallel to the rolling direction of the titanium copper foil can be reduced.

[0017] (composition) The Ti concentration of the titanium copper foil of the present disclosure is 1.5% by mass to 5.0% by mass. Titanium copper is dissolved in the Cu matrix by solution treatment, and fine precipitates are dispersed in the alloy by aging treatment, thereby increasing the strength and electrical conductivity. If the Ti concentration is less than 1.5% by mass, the precipitation of precipitates is insufficient and the desired strength cannot be obtained. If the Ti concentration exceeds 5.0% by mass, the workability is deteriorated and the material is easily cracked during rolling. Considering the balance between strength and workability, the Ti concentration is preferably 2.9% by mass to 4.3% by mass.

[0018] The titanium copper foil of the present disclosure may further contain one or more elements selected from the group consisting of Al, Ag, B, Co, Cr, Fe, Ge, Hf, La, Mg, Mn, Mo, Nb, Ni, P, Si, Sn, Y and Zr. However, such elements may not be contained. The total content of the element in the titanium copper foil may be 0.0 mass% to 1.0 mass%. If the content of the element is 1.0 mass% or less, deterioration of workability can be prevented.

[0019] The composition of titanium copper foil is confirmed by ICP optical emission spectrometry (internal standard method). Measurements are performed using an ICP optical emission spectrometry device (ICP-OES, inductively coupled plasma optical emission spectrometry device) such as Hitachi High-Tech Science's SPS3100 or an equivalent device. For ICP optical emission spectrometry, a titanium copper foil sample is dissolved in a mixed acid containing hydrochloric acid, nitric acid, and water in a volume ratio of 2:1:2, and then diluted. Y (yttrium) is used as the internal standard element.

[0020] (Foil thickness) The thickness of the titanium copper foil of the present disclosure can be evaluated by measuring the foil thickness at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction. In this disclosure, the average foil thickness at the nine points is also simply referred to as the "average foil thickness." In this disclosure, the standard deviation of the foil thickness at the nine points is also simply referred to as the "standard deviation of the foil thickness."

[0021] As described above, in the titanium copper foil of the present disclosure, the ratio of the standard deviation σ of the foil thickness to the average foil thickness tave (i.e., the value obtained by dividing the standard deviation σ of the foil thickness by the average foil thickness tave, σ / tave) is 0.0100 or less. The ratio of the standard deviation σ of the foil thickness to the average foil thickness tave may be preferably 0.0050 or less, and more preferably 0.0030 or less.

[0022] In the titanium copper foil of the present disclosure, the average foil thickness tave may be 200 μm or less, or may be 80 μm or less. In the titanium copper foil of the present disclosure, the lower limit of the average foil thickness tave is not particularly limited, but may be 20 μm or more. The average foil thickness tave of the titanium copper foil of the present disclosure may be 20 μm to 100 μm, or may be 40 μm to 80 μm.

[0023] In the titanium copper foil of the present disclosure, the standard deviation σ of the foil thickness may be 0.500 μm or less, or may be 0.200 μm or less.

[0024] With the miniaturization of electronic devices in recent years, titanium copper foils used in electronic devices may be required to have a thin foil thickness. On the other hand, when a titanium copper foil with a thin foil thickness is used in an electronic device, minute variations in the foil thickness may affect the performance or defects of the electronic device. For example, when titanium copper foil is used as a terminal of a connector, if the foil thickness is not sufficiently uniform in the longitudinal direction of the titanium copper foil (which may correspond to the "direction parallel to the rolling direction"), the contact pressure of each terminal may vary. As a result, there is a concern that poor contact may occur. In addition, for example, when used as a spring material, if the foil thickness of the titanium copper foil is sufficiently uniform, the stress applied to the spring material is easily dispersed. As a result, the fatigue resistance of the electronic component is improved. The titanium copper foil of the present disclosure can be used as a spring material in electronic components such as autofocus camera modules. In this case, the electronic component includes titanium copper foil.

[0025] The contact pressure P of each terminal of the connector is calculated by the formula: P = (d x E x w x t 3 ) / (4×L 3) where d is the amount of displacement (mm), E is Young's modulus (MPa), w is the width of the terminal (mm), t is the thickness of the terminal (mm), and L is the distance from the fixed end of the terminal to the contact position (mm). According to this formula, the contact pressure P of the connector is proportional to the cube of the terminal thickness t (i.e. the foil thickness of the titanium-copper foil), and it can be seen that the foil thickness has a large effect.

[0026] If the titanium copper foil of this embodiment has a small standard deviation σ of the foil thickness in the direction parallel to the rolling direction and reduced variation, the contact pressure of each terminal will be uniform, the contact resistance will be stable, and poor contact can be suppressed.

[0027] The variation in contact pressure of a connector is sometimes defined as (Pmax-Pmin) / Pave, where Pmax is the maximum contact pressure, Pmin is the minimum contact pressure, and Pave is the average contact pressure. If we assume that the maximum foil thickness can be simplified as tave+α and the minimum foil thickness can be simplified as tave-α, using a positive number α that is sufficiently smaller than the average foil thickness tave, the variation in contact pressure described above can be transformed into the following equation (1). If we ignore the third-order terms because α<<tave, the variation in contact pressure can be expressed as 6α / tave.

[0028]

number

[0029] To calculate the standard deviation σ of the foil thickness, the foil thickness is measured at n points located on a line at intervals of 10 mm along a direction parallel to the rolling direction of the titanium copper foil at the center position perpendicular to the rolling direction of the titanium copper foil, and the measured foil thickness values ​​(t1, t2...tn) are obtained. Then, the average value tave is calculated from the measured foil thickness values ​​(t1, t2...tn), and the standard deviation σ is calculated using the following formula (2). The foil thickness can be measured, for example, using a thickness meter attached to the rolling mill while rolling or while unrolling the titanium copper foil from the strip material. In the present disclosure, n=9.

[0030]

number

[0031] It is preferable that the standard deviation σ (μm) of the foil thickness and the average foil thickness tave (μm) of the titanium copper foil satisfy the relationship σ / tave≦0.0055. The basis for this is as follows.

[0032] Using statistical theory, when the variation in foil thickness has a normal distribution, the probability that the foil thickness t deviates from the range of tave ± 3σ is 0.3%. Furthermore, when the variation in contact pressure is 10%, 6α / tave = 0.1, so α = tave / 60. Therefore, when 3σ≦α is satisfied, that is, when σ / tave≦0.0055 according to the following formula (3), the probability that the variation in contact pressure when mounted on a connector terminal will exceed 10% can be suppressed to 0.3% or less. Similarly, when 4σ≦α (defect rate≦0.006%) is considered, it is even more preferable that the standard deviation of foil thickness σ (μm) and the average foil thickness tave (μm) satisfy σ / tave≦0.0041. However, there are cases where 0.001≦σ / tave≦0.0055.

[0033]

number

[0034] In the titanium copper foil of the present disclosure, the difference R between the maximum and minimum values ​​of the foil thickness measured at the above-mentioned nine points may be 2.00 μm or less, preferably 1.20 μm or less, and more preferably 0.50 or less.

[0035] In the titanium copper foil of the present disclosure, the difference R (μm) and the average foil thickness tave (μm) may satisfy the relationship R / tave≦0.033, which was calculated from the following formula (4) using R≦2α and α (=tave / 60) when the variation in contact pressure is 10%.

[0036]

number

[0037] The titanium copper strip of the present disclosure is a strip material in which titanium copper foil is wound into a coil shape, and includes the titanium copper foil described above. In other words, the titanium copper strip may include, at least in a portion thereof, a titanium copper foil in which the ratio (σ / tave) of the standard deviation σ (μm) of the foil thickness to the average foil thickness tave (μm) at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction is 0.0100 or less. The titanium copper foil of the remaining portion of the titanium copper strip may also have a σ / tave of 0.0100 or less, but it may also be a value larger than that.

[0038] The titanium copper foil in at least a part of the titanium copper strip has a σ / tave of 0.0050 or less, and preferably 0.0030 or less. The titanium copper foil in at least a part of the titanium copper strip has a standard deviation σ of 0.500 μm or less, and preferably 0.200 μm or less. The titanium copper foil in at least a part of the titanium copper strip has an average tave of 200 μm or less, and preferably 80 μm or less. The titanium copper foil in at least a part of the titanium copper strip has a difference between the maximum foil thickness and the minimum foil thickness of 2.00 μm or less, and preferably 1.20 μm or less.

[0039] (Tensile strength) The tensile strength of the titanium copper foil may be preferably 900 MPa or more, more preferably 1000 MPa or more. The tensile strength means the tensile strength in the direction parallel to the rolling direction of the titanium copper foil.

[0040] The tensile strength is measured in accordance with JIS Z2241 (2011) (Method of tensile testing of metal materials). For the measurement, a JIS 13B test piece is prepared from the titanium copper foil sample using a press machine. The conditions for the tensile test are as follows: test piece width: 12.7 mm, room temperature: 15 to 35°C, tensile speed (crosshead displacement speed): 5 mm / min, and gauge length (gauge length): 50 mm.

[0041] (Manufacturing method) An example of a method for producing the titanium copper foil of the present disclosure is as follows. First, a copper raw material such as electrolytic copper is melted together with the raw materials of Ti and other additive elements in a melting furnace to obtain a molten metal having a desired composition. The molten metal is then cooled and solidified, and an ingot is cast. In order to prevent oxidation wear of Ti, it is preferable to perform the melting and casting in a vacuum or inert gas atmosphere.

[0042] The obtained ingot is processed into a long strip material having a relatively thin thickness by, for example, sequentially performing a homogenization annealing step and a hot rolling step. The homogenization annealing step and the hot rolling step may be performed under the conventional conditions used in the manufacture of titanium copper foil.

[0043] Thereafter, the strip material is subjected to a cold rolling step and a heat treatment step. The cold rolling step is performed once or more, and typically, the cold rolling step and the heat treatment step are repeated multiple times. When the cold rolling step is performed three or more times, the cold rolling step includes a first cold rolling step, a final cold rolling step, and an intermediate cold rolling step between the first cold rolling step and the final cold rolling step. The heat treatment step includes a solution treatment step, an aging treatment step, etc.

[0044] In many cases, the cold rolling process uses a rolling mill in which a pair of rolls is arranged between a pay-out reel on which a strip material is wound and a take-up reel that takes up the strip material paid out from the pay-out reel. In this type of rolling mill, the strip material paid out from the pay-out reel is rolled by passing between the rolls, and then taken up by the take-up reel.

[0045] In the cold rolling process, the roll gap between a pair of rolling rolls is adjusted so that the strip material has a desired thickness after rolling. This roll gap adjustment can be performed as follows. The thickness of the strip material before rolling is detected at a predetermined point between the payout reel and the rolling rolls, and the time it takes for that point to reach between the rolling rolls is calculated from the feed speed of the strip material. Then, the roll gap is determined according to the thickness of the strip material before rolling.

[0046] Conventionally, the feed speed of the strip material when adjusting the roll gap has been calculated from the peripheral speed of the rolling roll, not an actually measured value. In this case, if slippage occurs between the rolling roll and the strip material, the indirect feed speed calculated from the peripheral speed of the rolling roll will deviate from the actual feed speed. As a result, the roll gap is not adjusted properly, and the rolling accuracy of the strip material decreases. Therefore, it becomes difficult to obtain a strip material having a desired thickness.

[0047] In contrast, in this embodiment, the feed speed of the strip material is measured by a laser speedometer arranged between the payout reel and the rolling roll, and the roll gap between the rolling rolls is adjusted using the measured feed speed. In this way, the feed speed of the strip material is directly measured and the roll gap is adjusted using the measured feed speed, so that the strip material is not affected by the above-mentioned slippage. As a result, the strip material can be rolled in its longitudinal direction with high accuracy. Therefore, the foil thickness of the titanium copper foil produced in the direction parallel to the rolling direction is sufficiently uniform.

[0048] The rolling mill may be equipped with an automatic thickness control mechanism that automatically controls the thickness of the strip material. In this case, it is preferable to configure the automatic thickness control mechanism so that the measured value of the feed speed of the strip material obtained by the laser speedometer is sent to the automatic thickness control mechanism and the roll gap is adjusted based on the measured value. This allows the adjustment of the roll gap using the measured value of the laser speedometer as described above to be automatically controlled.

[0049] When the cold rolling process includes a first cold rolling process, an intermediate cold rolling process, and a final cold rolling process, it is preferable to adjust the roll gap using the measured value of the laser speedometer as described above at least in the intermediate cold rolling process. The above-mentioned high-precision roll gap adjustment does not need to be performed in the first cold rolling process, but it is preferable to perform it not only in the intermediate cold rolling process but also in the final cold rolling process. When producing titanium copper foil, the intermediate cold rolling process often performs multiple passes of rolling, so the foil thickness variation during the first cold rolling process can be sufficiently corrected. The processing degree of the final cold rolling process is often smaller than the processing degree of the intermediate cold rolling process, and if the foil thickness variation is sufficiently corrected in the intermediate cold rolling process, it is considered that the correction effect of the foil thickness variation in the final cold rolling process is relatively small.

[0050] The rolling reduction ratio (%) is the thickness before rolling T 0、 When the thickness after rolling is T1, it is calculated by (T0-T1) / T0×100.

[0051] The reduction ratio in the intermediate cold rolling step may be 55% or more, further 60% or more, particularly 65% ​​or more, or may be less than 99.8% for the purpose of improving strength, etc. The reduction ratio in the intermediate cold rolling step may be 55% or more and less than 99.8%.

[0052] The reduction ratio of the final cold rolling step may be 5% or more, further 10% or more, particularly 15% or more, and may be less than 99.8%. The reduction ratio of the final cold rolling step may be 5% or more and less than 99.8%. The reduction ratio of the final cold rolling step may be less than the reduction ratio of the intermediate cold rolling step.

[0053] Conventional conditions can be adopted as the conditions for the cold rolling process and the conditions for the other processes.

[0054] In the solution treatment step, heating may be performed at 700° C. to 1000° C., typically 800° C. to 950° C., for 5 seconds to 30 minutes, typically 5 seconds to 300 seconds (5 minutes).

[0055] After carrying out each of the above-mentioned steps, the surface may be subjected to pickling, polishing, or the like, as necessary, in order to remove the oxide film or oxide layer formed on the surface.

[0056] (Application) The titanium copper foil of the present disclosure can be suitably used as a material for electronic components such as switches, connectors, jacks, terminals, relays, autofocus camera modules, etc. for electronic devices. The titanium copper foil of the present disclosure is particularly suitable as a material for connectors. However, the applications are not limited to these. EXAMPLES

[0057] The titanium copper foil of the present disclosure was actually produced as a prototype and its performance was evaluated, which will be described below. However, the description here is merely for illustrative purposes and is not intended to be limiting.

[0058] First, electrolytic copper and Ti raw material were melted in a vacuum melting furnace to produce an ingot with a predetermined Ti concentration. This ingot was hot rolled to produce a strip material with a thickness of 10 mm. Next, the strip material was first cold rolled to produce a strip material with a thickness of 1.5 mm. Next, heat treatment and cold rolling were repeated to produce a strip material with a thickness of 0.060 mm. Cold rolling was performed three times, including first cold rolling, intermediate cold rolling, and final cold rolling. Thereafter, the surface was pickled and polished to obtain a titanium copper foil.

[0059] In Comparative Example 1, the feed speed of the strip material was calculated from the peripheral speed of the rolling roll in intermediate cold rolling, and the roll gap was adjusted using this calculated value. On the other hand, in Example 1, the feed speed of the strip material was directly measured using a laser speedometer in intermediate cold rolling, and the roll gap was adjusted using the measured value. As described above, the manufacturing conditions of Comparative Example 1 and Example 1 were substantially the same, except for the method of adjusting the roll gap in intermediate cold rolling.

[0060] The components of the titanium copper foil were confirmed by ICP emission spectrometry (internal standard method) as described above. In addition, the foil thickness was measured at nine points located on a straight line at intervals of 10 mm in the direction parallel to the rolling direction for each of the titanium copper foils of Comparative Example 1 and Example 1. The results are shown in Table 1.

[0061] To measure the foil thickness, a Nikon digital microscope MH-15M was used, along with a TC-101A counter, an MS-5C measuring stand, and a standard gauge head. After setting the digital microscope so that the gauge head could move vertically, the zero point was adjusted, and the titanium copper foil was placed on the measuring stand and the foil thickness was measured while applying a downward measuring force of 0.637N.

[0062] In Table 1, (tmax 3 -tmin 3 ) / tave 3 Regarding ×100, as mentioned above, the contact pressure P of the connector is calculated by the formula: P = (d × E × w × t 3 ) / (4×L 3 ). The variation in the contact pressure of the connector can be evaluated by (Pmax-Pmin) / Pave. Here, Pmax is the maximum contact pressure, Pmin is the minimum contact pressure, and Pave is the nominal contact pressure. If the above formula is transformed by setting t=tmax when Pmax, t=tmin when Pmin, and t=tave when Pave, then (Pmax-Pmin) / Pave=(tmax 3 -tmin 3 ) / tave 3 This is expressed as a percentage and used as a parameter to evaluate the variation in the contact pressure of the connector. 3 -tmin 3 ) / tave 3 The smaller the value of x100, the smaller the variation in the connector contact pressure.

[0063] [Table 1]

[0064] As shown in Table 1, in Example 1, the feed speed of the strip material was directly measured using a laser speedometer in the cold rolling process, and the roll gap was adjusted based on the measured value. This resulted in smaller standard deviations σ and σ / tave of the foil thickness compared to Comparative Example 1, in which the roll gap was adjusted using the feed speed of the strip material calculated from the peripheral speed of the rolling rolls. In addition, the difference R between the maximum and minimum foil thicknesses and R / tave were also smaller. As a result, (tmax 3 -tmin 3 ) / tave 3 The x100 value has been reduced.

[0065] From the above, it has been found that the titanium copper foil manufacturing method of the present disclosure can produce a titanium copper foil with sufficiently reduced variation in foil thickness. Therefore, the embodiment of the present invention can have the following aspects. [1] Contains 1.5% by mass to 5.0% by mass of Ti, with the remainder being copper and unavoidable impurities; A titanium copper foil, in which the ratio of the standard deviation (μm) of the foil thickness to the average value (μm) of the foil thickness at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction is 0.0100 or less. [2] The titanium copper foil according to [1], wherein the ratio of the standard deviation of the foil thickness to the average foil thickness is 0.0050 or less. [3] The titanium copper foil according to [2], wherein the ratio of the standard deviation of the foil thickness to the average foil thickness is 0.0030 or less. [4] The titanium copper foil according to any one of [1] to [3], wherein the standard deviation of the foil thickness is 0.500 μm or less. [5] The titanium copper foil according to [4], wherein the standard deviation of the foil thickness is 0.200 μm or less. [6] The titanium copper foil according to any one of [1] to [5], wherein the average foil thickness is 200 μm or less. [7] The titanium copper foil according to [6], wherein the average foil thickness is 80 μm or less. [8] The titanium copper foil according to any one of [1] to [7], wherein the difference between the maximum foil thickness and the minimum foil thickness is 2.00 μm or less. [9] The titanium copper foil according to [8], wherein the difference between the maximum foil thickness and the minimum foil thickness is 1.20 μm or less.

[10] The titanium copper foil according to any one of [1] to [9], wherein the total content of at least one element selected from the group consisting of Al, Ag, B, Co, Cr, Fe, Ge, Hf, La, Mg, Mn, Mo, Nb, Ni, P, Si, Sn, Y and Zr is 0.0 mass% to 1.0 mass%.

[11] Contains 1.5% by mass to 5.0% by mass of Ti, with the remainder being copper and unavoidable impurities; A titanium copper foil in which the standard deviation of the foil thickness at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction is 0.500 μm or less.

[12] The titanium copper foil according to

[11] , wherein the standard deviation of the foil thickness is 0.200 μm or less.

[13] The titanium copper foil according to

[11] or

[12] , wherein the total content of at least one element selected from the group consisting of Al, Ag, B, Co, Cr, Fe, La, Mg, Mn, Mo, Nb, Ni, P, Si, Sn, Y and Zr is 0.0 mass% to 1.0 mass%.

[14] A titanium copper strip comprising the titanium copper foil according to any one of [1] to

[13] .

[15] An electronic component comprising the titanium copper foil according to any one of [1] to

[13] .

Claims

1. Contains 1.5% by mass to 5.0% by mass of Ti, with the balance being copper and unavoidable impurities; A titanium copper foil, in which the ratio of the standard deviation (μm) of the foil thickness to the average value (μm) of the foil thickness at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction is 0.0100 or less.

2. 2. The titanium copper foil according to claim 1, wherein the ratio of the standard deviation of the foil thickness to the average foil thickness is 0.0050 or less.

3. 3. The titanium copper foil according to claim 2, wherein the ratio of the standard deviation of the foil thickness to the average foil thickness is 0.0030 or less.

4. 2. The titanium copper foil according to claim 1, wherein the standard deviation of the foil thickness is 0.500 μm or less.

5. The titanium copper foil according to claim 4, wherein the standard deviation of the foil thickness is 0.200 μm or less.

6. The titanium copper foil according to claim 1 or 4, wherein the average foil thickness is 200 μm or less.

7. The titanium copper foil according to claim 6, wherein the average foil thickness is 80 μm or less.

8. The titanium copper foil according to claim 1 or 4, wherein the difference between the maximum foil thickness and the minimum foil thickness is 2.00 μm or less.

9. 9. The titanium copper foil according to claim 8, wherein the difference between the maximum foil thickness and the minimum foil thickness is 1.20 μm or less.

10. The titanium copper foil according to claim 1 or 4, wherein the total content of at least one element selected from the group consisting of Al, Ag, B, Co, Cr, Fe, Ge, Hf, La, Mg, Mn, Mo, Nb, Ni, P, Si, Sn, Y and Zr is 0.0% by mass to 1.0% by mass.

11. Contains 1.5% by mass to 5.0% by mass of Ti, with the balance being copper and unavoidable impurities; A titanium copper foil having a standard deviation of foil thickness of 0.500 μm or less at nine points located on a straight line at intervals of 10 mm in a direction parallel to the rolling direction.

12. 12. The titanium copper foil of claim 11, wherein the standard deviation of the foil thickness is 0.200 μm or less.

13. The titanium copper foil according to claim 11 or 12, wherein the total content of at least one element selected from the group consisting of Al, Ag, B, Co, Cr, Fe, Ge, Hf, La, Mg, Mn, Mo, Nb, Ni, P, Si, Sn, Y and Zr is 0.0% by mass to 1.0% by mass.

14. A titanium copper strip comprising the titanium copper foil according to claim 1 or 11.

15. An electronic component comprising the titanium copper foil according to claim 1 or 11.

Citation Information

Patent Citations

  • Titanium copper foil and manufacturing method therefor

    JP2017179570A

  • Titanium copper foil and method for producing titanium copper foil

    JP2020157363A